Willingness to pay for climate change mitigation: college students’ perceptions in Tennessee and Kentucky - Tewari, Rachna (Advances in Social Sciences Research Journal, 2020)
Climate change and its impact on agriculture and rural communities has been a much-discussed topic among scientists, academics, and the general public. Existing studies have revealed a disconnect between agricultural stakeholders and the wider climatological community in the U.S., which impacts the process of making informed decisions in response to climate related issues in agriculture. This study evaluates college students’ perspectives about global warming and climate change in two agricultural schools located in western Tennessee and western Kentucky, respectively. Data was collected using a Likert scale survey tool and questions ranged from awareness of specific climate change terms, mitigation efforts, and the level of concern for such efforts. Ultimately, this study analyzed differences in students’ perception of willingness to pay for climate change mitigation efforts as affected by demographics, concern about the impact of climate change on agriculture, and existing knowledge about climate change. Among other variables, the need for more information about climate change had a significantly positive impact on the willingness to make a financial contribution to climate change mitigation efforts. This study will potentially enhance existing literature on the future workforces’ perceptions for climate change mitigation efforts, which will in turn provide insights for policy recommendations.